The legacy of the forest: a source study of 'Wood' (2009) by Alice Munro. Issue 3 (4th March 2022) - Ventura, Héliane
ABSTRACT: This paper offers a reading of 'Wood' by Alice Munro, a short story originally published in The New Yorker in November 1980 and collected in her penultimate volume of short stories, Too Much Happiness in 2009. The interest of the story derives from its miniaturisation of world literature in a natural environment recognised as next of kin. Using the methodology of close textual reading, I have tried to elucidate some of its conundrums and more specifically discovered an intertextual reference to Khalil Gibran in the mysterious last sentence of the text. I have tried to highlight a few of the other sources Munro has resorted to in a story that summons the tradition of forest writing from Antiquity and the Medieval quest narrative up to contemporary nature writing. This deceptively simple story with epic ramifications renews the short story genre and our expectations of what literature can bring to our lives: rejuvenation and empowerment through the possibilities of rewriting the ordinary scripts of our ordinary existence against our 'naturalcultural' legacy.